2023
DOI: 10.3389/fendo.2023.1168936
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine as an adjuvant therapy in severe Graves’ disease: a randomized controlled open-label clinical trial

Abstract: IntroductionAzathioprine (AZA) interferes with the activation of T and B lymphocytes, which are the main cells involved in the pathogenesis of Graves’ disease (GD). The aim of this study was to investigate the effectiveness of AZA as an adjuvant therapy to antithyroid drugs (ATDs) for moderate and severe GD. In addition, we conducted an incremental cost-effectiveness analysis of AZA to determine its cost-effectiveness.MethodsWe conducted a randomized, open-label, and parallel-group clinical trial. We randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Azathioprine is a purine analog that also stops lymphoid proliferation. A recent study showed that the addition of azathioprine to ATD increased the remission rates from 33.4% to 87.5% [37]. Other clinical trials have used monoclonal antibodies to treat GD.…”
Section: Treatmentmentioning
confidence: 99%

Graves Disease - A Comprehensive Review

Phagoora,
Sarthak Bakilwal,
Arshia Hamzehpour S
et al. 2024
PJOM
“…Azathioprine is a purine analog that also stops lymphoid proliferation. A recent study showed that the addition of azathioprine to ATD increased the remission rates from 33.4% to 87.5% [37]. Other clinical trials have used monoclonal antibodies to treat GD.…”
Section: Treatmentmentioning
confidence: 99%

Graves Disease - A Comprehensive Review

Phagoora,
Sarthak Bakilwal,
Arshia Hamzehpour S
et al. 2024
PJOM
“…The results of the study are striking, with high remission rate of 87.5% among patients taking adjuvant azathioprine therapy (1). The American Thyroid Association (ATA) uses a remission criteria of being euthyroid for at least 12 months after withdrawing ATDs (4).…”
Section: Inconsistencies In Remission Criteriamentioning
confidence: 99%
“…We read the study by Allam and colleagues with interest, which studied the role of azathioprine as an adjuvant therapy to anti thyroid drugs (ATD) in patients with moderate and severe Graves' disease (GD) in a randomized controlled trial. The primary outcome of rate of remission after a follow up period of 2 years was compared among three randomized groups of patients, one on conventional therapy with ATDs and the other 2 on different doses of azathioprine in addition to conventional therapy (1). Currently recommended therapies for GD do not address the underlying immunopathogenesis of the disease and addition of immunosuppressives to standard treatment has been shown to improve relapse rates (2).…”
Section: Introductionmentioning
confidence: 99%
“…According to the study, the azathioprine (AZA)1 and AZA2 groups had a higher rate of remission (87.5% and 87.5% vs. 33.4%, p = 0.002) than the controls. The treatment did not significantly differ between the AZA and control groups throughout follow-up, but there were significant differences in FT3, FT4, TSH, and TRAb [ 15 ]. Furthermore, the AZA2 group experienced a significantly faster decline in FT4, FT3, and TRAb concentrations than the AZA1 group.…”
Section: Reviewmentioning
confidence: 99%